PREDISPOSING FACTOR OF MULTIDRUG-RESISTANT TUBERCULOSIS IN SARDJITO GENERAL HOSPITAL, YOGYAKARTA FROM 2009 TO 2012 - , AIDHA YUNIAR.P.H ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Tuberculosis (TB) is a growing global health problem, with increasing evidence of multidrug-resistant (MDR)-TB. By the year of 2012, out of the 8.6 million prevalent TB cases, around 450,000 were estimated to be multidrug-resistant. It is a serious threat to the goal achievement of the Stop TB partnership to eliminate TB as a public health problem by 2050, due to the complexities in diagnosis and treatment, and also the high treatment failure and mortality rates. Indonesia, with a population of around 230 million, carries the third highest TB burden globally. Indonesia also ranks 9th out of 27 countries with high burden MDR-TB. To our knowledge, for the past decade, there have been no data on these aspects of TB patients in Sardjito General Hospital Yogyakarta, and even in Yogyakarta. Therefore, we plan to establish a sufficient TB patient database to reveal the predisposing factor and prevalence of MDR-TB patients. This record will provide ample opportunity as a starting point of the future studies. Objective: The general objective of this study is to further observe and analyze the predisposing factor of MDRTB patients, especially those related with demographic feature and clinical information of the patients. Method: This study used a retrospective cohort method to determine correlation between the demographic feature and clinical information of TB patients who received treatment in Sardjito General Hospital between year of 2009 to 2012, and the development to MDR-TB. The data were obtained from the medical record. Result: From the 249 subjects, 13 (5,2%) patients considered as MDR-TB and 236 patients as sensitive TB. Patients with MDR-TB were slightly older and less likely to be male compared to sensitive TB patients. From the univariate analysis, previous treatment, DM, and organ involvement were considered significantly related to MDR-TB development with p value of <0,001, 0,021, and 0,017, respectively. In bivariate analysis, only DM considered as predisposing factor of MDR-TB (P= 0,038